Comprehensive dietary antioxidant index and chronic kidney disease: mediating role of frailty and its impact on mortality outcomes in adults - Li, Wenqing; Chen, Shuang; Wan, Jiangmin; Chen, Liyuan; Xing, Lingzhi; Gao, Zhenglan; Chen, Ling (Frontiers in Nutrition, 2025)
BackgroundChronic kidney disease (CKD) poses significant global health challenges, with oxidative stress and inflammation contributing to its pathogenesis. While dietary antioxidants may mitigate CKD risk, reflected by Comprehensive Dietary Antioxidant Index (CDAI), the mediating role of frailty (FI) remains underexplored. This study investigates the association between CDAI and CKD risk, with a focus on FI as a potential mediator and its implications for mortality outcomes.MethodsUtilizing data from 11,904 U. S. adults in the National Health and Nutrition Examination Survey (NHANES, 2011–2018), we analyzed CDAI (comprising manganese, selenium, zinc, and vitamins A, C, E) and its association with CKD. Multivariable logistic regression, restricted cubic splines, and Cox proportional hazards models assessed relationships between CDAI, FI, CKD, and mortality. Mediation analysis quantified FI’s role in CDAI-CKD associations.ResultsHigher CDAI scores were inversely associated with CKD prevalence (OR = 0.802, 95%CI [0.753, 0.854], p < 0.001), with a 46.6% lower CKD risk in the highest vs. lowest CDAI quartile. Frailty mediated 36% (95% CI: 35–38%) of the CDAI-CKD relationship. Manganese and vitamin C exhibited independent protective effects against CKD (p < 0.001). Survival analyses revealed lower CDAI correlated with higher all-cause mortality in pre-frail CKD patients (p = 0.030) and elevated cardiovascular mortality in frail patients (p < 0.0001). Vitamin E inversely linked to cardiovascular mortality (HR = 0.934, p = 0.019), while vitamin A increased risk (HR = 1.266, p = 0.005).ConclusionComprehensive Dietary Antioxidant Index is inversely associated with CKD risk, partially mediated by FI. Dietary antioxidant intake, particularly vitamins C and E, may improve outcomes in CKD populations, especially those with frailty. These findings highlight the potential of nutritional interventions to mitigate CKD progression and mortality. Further randomized trials are needed to confirm causality and optimize dietary strategies for high-risk groups.